“The place incidence in the Chapel of Ronchamp” (2019)
The Chapel of Ronchamp was originated in one of Le Corbusier’s first visits to the place. At first, it seemed like a spontaneous birth, but in fact it took many years of incubation through the alternate exercises that the swiss master maintained through painting and sculpture, especially by a concept that he called the ‘acoustic form’ phenomenon, which was related to forms that were put in close relation with the surrounding space.